A highly flexible transparent conductive electrode based on nanomaterials - Kim, Chang-Lae; Jung, Chan-Won; Oh, Young-Jei; Kim, Dae-Eun (NATURE PUBLISHING GROUP, 2017)
The electrical, optical, thermal, chemical, mechanical and tribological characteristics of a highly flexible transparent conductive electrode (HFTCE) coating based on reduced graphene oxide (rGO), carbon nanotubes (CNTs) and silver nanowires (AgNWs) were investigated under various conditions. The motivation was to develop a highly durable and flexible film for transparent conductive electrode applications. The overall characteristics of multilayers based on rGO, CNTs and AgNWs were found to be much better than those of the single-layer AgNW coating. The rGO and CNT layers served to protect the AgNW layer from damage due to bending and contact sliding motions. The contact pressure and bending stress were effectively distributed by the CNT layer deposited on top of the AgNW layer due to its spring-like behavior. In addition, the shear force from the friction force was reduced by the rGO top layer, which acted as a solid lubricant. Furthermore, the excellent performance of an HFTCE heater based on the rGO/CNT/AgNW coating was demonstrated by the results of a defrosting test.
Keywords: REDUCED GRAPHENE OXIDE; SILVER NANOWIRES; CARBON NANOTUBES; SOLAR-CELLS; FRICTIONAL BEHAVIOR; FILM HEATERS; PERFORMANCE; COMPOSITE; SILICON; REDUCTION